2022
DOI: 10.3390/en15041562
|View full text |Cite
|
Sign up to set email alerts
|

Research on Constant Voltage/Current Output of LCC–S Envelope Modulation Wireless Power Transfer System

Abstract: As a technology that makes power transfer more flexible, wireless power transfer (WPT) technology has become a hot research topic in recent years. However, most of the existing studies are based on a DC–DC WPT system. If applied to AC loads, the traditional system usually contains multiple energy conversion stages, which lead to a low transmission efficiency and therefore higher costs. Besides, the necessary large electrolytic capacitors make the system unreliable and bulky. The goal of this study is to design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Some authors support their conclusions using finite element analysis as reported, for example, in [21]. The literature reports numerous works [22,23] dealing with the same issue, but the emphasis is on WPT systems' driving and regulation [24][25][26][27].…”
Section: Introductionmentioning
confidence: 63%
“…Some authors support their conclusions using finite element analysis as reported, for example, in [21]. The literature reports numerous works [22,23] dealing with the same issue, but the emphasis is on WPT systems' driving and regulation [24][25][26][27].…”
Section: Introductionmentioning
confidence: 63%
“…A compensation network is used on both the GA and VA coils to achieve the resonance condition in order to improve the electrical performance. On the receiving side, the VA coil is connected to the compensation network and to a rectifier, which transforms the high-frequency voltage into direct voltage used to recharge the battery [36][37][38][39][40][41][42][43]. For the analysis of the magnetic coupling and system performances, an equivalent simplified circuit can be adopted, as shown in Figure 2.…”
Section: Dwpt Equivalent Circuitmentioning
confidence: 99%
“…For instance, the Series‐Series (SS) compensation is characterized by high transmission efficiency at low coupling coefficients and operates approximately as a current source [11]. On the other hand, the LCC‐S compensation, which is receiving relevant attention lately, achieves better results at higher coupling coefficients and operates approximately as a voltage source [12]. Each topology exploits the resonance phenomenon: inductances and capacitors are tuned to resonate at a particular frequency, minimizing the reactive power and maximizing the active power transmission [13].…”
Section: Introductionmentioning
confidence: 99%